RANCANG BANGUN APLIKASI MONITORING DAN EVALUASI PELANGGARAN SISWA PADA SMAN 14 SURABAYA BERBASIS WEB - Lay, Filmon Andrean; Ayuningtyas, Ayuningtyas; Lemantara, Julianto (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2018)
In the teaching-learning process, student violation often occurs, the handling of which would need parent involvement. However, parent involvement is still minimal to date, since the parent would only be aware of the violation when they receive the warning letter from the school. In addition, with the number of student violation keeps increasing day after day, miscalculation often occurs in the violation data recapitulation which is conducted quarterly, all to the disadvantage of the student in terms of the sanction applied by the school.To ascertain that the process of handling student violation can run smoothly, SMAN 14 Surabaya has established a student violation monitoring and evaluation application for purposes of recording, directing and supervising student development during the teaching-learning process at school.With this application, the monitoring and evaluation process can be achieved due to the function of the dashboard in the application which can show the percentage of violating actions; and there are also recommendation and evaluation proposed by the school, and the school may also issue warning letters in a real-time manner without having to wait for the quarter data recapitulation. The application may also send out notifications in the form of SMS to the parent, and either the parent or the student may access the student violation report to see the detail of the violation.